Are bulling behaviors tolerated in some cultures? Relationship between workplace bullying and job satisfaction among Azerbaijani employees - Huseynli, Ulkar; Asgarova, Aygun (ADA University, 2020)
Our study adopted the article “Are bullying behaviors tolerated in some cultures? Evidence for a curvilinear relationship between workplace bullying and job satisfaction among Italian workers” from the journal of Business Ethics Vol. 131, No. 1 (September 2015), for replication of the same or similar analysis for Azerbaijan. The aim of this study was to determine whether the same curvilinear effect can be observed in a sample of Azerbaijani employees. As this was the first study in this context in our country, we aimed to address different sectors for conducting the analysis. Supporting the replication study, our results demonstrated curvilinear relationship between workplace bulling and job satisfaction. On the other hand, psychological well-being demonstrated linear relationship in contrast to curvilinear model between workplace bulling and job satisfaction. In particular, our purpose is to study whether victims of bulling try to determine the causes taking into consideration social and cultural norms. We aimed to explore if the workplace bulling is tolerated to some extent among Azerbaijani workers. Our results supported the view that, it is important to consider cultural and organizational factors in order to better understand and deal with workplace bulling.
Keywords: Business; Conflict management.; Organizational behavior.; Interpersonal conflict.; Problem employees -- Psychology.; Personnel management -- Psychological aspects.